Innovation and Innovative Solutions Through Partnerships - Misra, Renu; Parashar, Neha (Prabandhan: Indian Journal of Management, 2008)
The world is becoming more interconnected and organizations that want to succeed in this new environment need to become more connected as well. It is a challenge to individuals, teams, businesses, and the wider world. To innovate, many high performing firms are collaborating beyond their organizations with their extended networks of suppliers, customers, business partners and others. This Paper tries to examine the role of organizational partnership on innovation. In this paper we reviewed various research work done on collaborative innovation. The purpose of this paper is to examine recent patterns and developments in the literature on innovations in business through collaboration.